Boosting India’s citrus industry: ICAR-CCRI introduced elite exotic varieties from the USA - Kadam, Darshan M; Ghosh, Dilip (Indian Horticulture, 2025)
The ICAR-CCRI, Nagpur, has introduced 16 elite exotic citrus varieties from the USDA’s National Clonal Germplasm Repository for Citrus and Dates, Riverside, California. These include six sweet oranges (Bahianinha, Frost, Lima, Midknight, Olympic Gold, and Salustiana), three mandarins (Pixie, Shasta Gold, and Tahoe Gold), Australian finger lime (Microcitrus australasica), a pummelo hybrid(Cocktail), tangor (King), tangelo (Minneola), and three rootstocks (Flying Dragon, C-35, and Troyer). Known for superior yield, premium quality, and extended harvesting windows, these varieties address challenges in India’s citrus industry such as low productivity, limited varietal diversity, and subpar fruit quality. Performance trials across diverse agro-climatic zones are underway,with anticipated outcomes including higher yields, enhanced profitability, and improved global competitiveness for India’s citrus sector.